1990
DOI: 10.2307/1130851
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Sensitivity and the Security of Infant-Mother Attachment: A Q-Sort Study

Abstract: 40 mothers and their 12-month-old infants were observed twice at home by 2 observers for 2 hours. After the second visit, the observers described the infant using the Waters Attachment Behavior Q-sort and the mother's interactive behavior with the Maternal Behavior Q-sort developed by the present authors and Ainsworth's rating scales. Maternal sensitivity was unrelated to maternal age, income, or SES, but correlated positively with maternal education. Mothers of more difficult children were less sensitive. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
151
1
24

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 249 publications
(190 citation statements)
references
References 7 publications
13
151
1
24
Order By: Relevance
“…Matemal sensitivity, however, is not related to social class, incorne, occupational status, matemal age, or infant age (Moran et al, 1992;Pederson et al, 1990). The relation between sensitivity and educational level is unclear; it has been found to be both related (Pederson et al,1 WO), and unrelated ( Moran et al, 1992) to sensitivity.…”
Section: Environmentai Contextuai Variablesmentioning
confidence: 99%
See 3 more Smart Citations
“…Matemal sensitivity, however, is not related to social class, incorne, occupational status, matemal age, or infant age (Moran et al, 1992;Pederson et al, 1990). The relation between sensitivity and educational level is unclear; it has been found to be both related (Pederson et al,1 WO), and unrelated ( Moran et al, 1992) to sensitivity.…”
Section: Environmentai Contextuai Variablesmentioning
confidence: 99%
“…While these measures tend to be more consistent than behaviorai scaies, they are broad and do not provide much information about individuai differences. Use of these scales also requires the observer to have an understanding of the mother's psychologicai processes and the infant's needs, and observations must be carried out in situations in which subtle attributes can be discemed (Pederson et al, 1990).…”
Section: Assessrnent Of Matemal Sensitivitymentioning
confidence: 99%
See 2 more Smart Citations
“…Maternal responsiveness has proven the most robust predictor of infants' patterns of attachment (see Pederson et al, 1990 ), which in turn predict social adjustment and relationship patterns at least into adolescence (the current general age of the first participants being followed in longitudinal attachment research since infancy). Other research has shown that parents' attachment patterns vis-à-vis their own parents are highly predictive of their unborn infants' later patterns of attachment to them, documenting the impact of parental attachment style on the child's developing experience of relationships ( Fonagy, Steele, & Steele, 1991 ;H.…”
Section: The Role Of Childhood Experiencesmentioning
confidence: 99%